Nomogram Based on Hemoglobin, Albumin, Lymphocyte and Platelet Score to Predict Overall Survival in Patients with T3-4N0-1 Nasopharyngeal Carcinoma - Zhao R; Liang Z; Chen K; Zhu X (Dove Medical Press, 2023)
Rong Zhao,1 Zhongguo Liang,1 Kaihua Chen,1 Xiaodong Zhu1- 3 1Department of Radiation Oncology, Guangxi Medical University Cancer Hospital, Nanning, Guangxi, People's Republic of China; 2Affiliated Wu-Ming Hospital of Guangxi Medical University, Nanning, Guangxi, People's Republic of China; 3Key Laboratory of Early Prevention and Treatment for Regional High Frequency Tumor (Guangxi Medical University), Ministry of Education/Guangxi Key Laboratory of Early Prevention and Treatment for Regional High Frequency Tumor, Nanning, Guangxi, People's Republic of ChinaCorrespondence: Xiaodong Zhu, Email zhuxdonggxmu@126.comPurpose: There is still uncertainty regarding the prognosis of nasopharyngeal carcinoma (NPC) based on hemoglobin, albumin, lymphocytes, and platelets (HALP) score. The aim of this study was to build and verify a nomogram using HALP score to investigate the prognostic value of NPC and identify low-risk patients in T3-4N0-1 NPC to guide treatment options.Patients and methods: A total of 568 NPC patients with stage T3-4N0-1M0 were recruited in the study, who were given either concurrent chemoradiotherapy (CCRT) or induction chemotherapy (IC) plus CCRT. The prognostic factors of overall survival (OS) were picked by Cox proportional hazards regression analysis to generate a nomogram, which appraised by discrimination, calibration and clinical utility. Patients were stratified according to risk scores calculated by the nomogram, and compared to the 8th TNM staging system using the Kaplan-Meier methods.Results: Multivariate analysis showed that TNM stage, Epstein-Barr virus DNA (EBV DNA), HALP score, lactate dehydrogenase-to-albumin ratio (LAR) and systemic inflammatory response index (SIRI) were independent prognostic indicators for OS, and these factors contained in the nomogram. The nomogram demonstrated a significant enhancement over the 8th TNM staging system in terms of assessing OS (C-index, 0.744 vs 0.615 in the training cohort, P < 0.001; 0.757 vs 0.646 in the validation cohort, P = 0.002). Calibration curves displayed good agreement and the stratification in high-risk and low-risk groups resulted in a significant divergence of Kaplan-Meier curves for OS (P < 0.001). In addition, the decision analysis (DCA) curves confirmed satisfactory discriminability and clinical utility.Conclusion: The HALP score was an independent prognostic factor for NPC. The prognostic function of the nomogram for T3-4N0-1 NPC patients was more accurate compared to the 8th TNM system, facilitating personalized treatment planning.Keywords: Epstein-Barr virus, induction chemotherapy, concurrent chemoradiotherapy, locoregional extension patterns, immunoinflammatory marker